UTILIZATION OF BENUAS RESIDUAL SAWDUST FROM SAWMILL INDUSTRY AS MATERIALS FOR PAVING BLOCK - Patrisia, Yulin; Cassiophea, Lola (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2013)
Concrete paving block for flooring is widely used as a material for the road pavement on campus, offices, sidewalks, roads, parking areas and so forth. This may imply that the use of paving blocks are so complex, so the need increases due to the practicality of installation and maintenance. Various attempts were made in an effort to improve the quality as a result of market competition of the paving block. As an alternative to improve the quality is the addition of sawdust in the manufacture of paving blocks. The purpose of this study was to determine the wear and tear, porosity and compressive strength of paving blocks with the addition of sawdust. The method used is an experimental method. Therefore, the study was obtained through the compressive strength, porosity and wear resistance by comparing the paving block that use the sawdust and without sawdust. The results showed the effect of adding sawdust to the compressive strength of paving blocks. For 5% sawdust addition , the results of the compressive strength of paving blocks are relatively the same as the compressive strength of paving blocks 0 % sawdust. But for the addition of 10 % and 15% sawdust, the decrease the compressive strength of paving blocks increasing significantly. The effect of the addition of sawdust on porosity and wear resistance is the higher sawdust paving block composition is, the higher porosity and the lower the wear resistance of paving blocks will be.